"From war to peace": Military festival visitors' quality-of-life. Issue 3 (4th May 2019) - Venter, Dewald; Kruger, Stefan
Abstract : The Voortrekker Monument Military festival is one of several military festivals held in South Africa. This study sought to determine the travel motives and life domain effects on the quality-of-life of visitors. Data were gathered from 330 visitors on their travel motives, overall life domains, and quality-of-life. Structural Equation Modelling analysis indicated a positive linear relationship between the visitors' travel motives, life domains (social-life, leisure-life, and self-life), life domains overall, and quality-of-life; all of which attained good reliabilities. The findings indicate that a visit to a military heritage festival has a positive effect on visitors' quality-of-life. This research adds to literature in the social sciences, positive psychology, and quality-of-life.